Composite material based on degradable plastic PBAT and preparation method thereof

By reasonably mixing and preparing polyamide sheet crystals with PBAT, polyamide sheet crystals/PBAT composites are formed, which solves the problem of low mechanical strength of PBAT, and achieves significant improvement in material strength and toughness while maintaining degradability.

CN119613928APending Publication Date: 2025-03-14HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411967379.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The biodegradable plastic PBAT has a problem of low mechanical strength in applications, which limits its promotion and application.

Method used

By reasonably mixing and preparing the polyamide sheet crystals with PBAT, polyamide sheet crystals/PBAT composite material is formed, and the solution or melt of PBAT is mixed with the polyamide sheet crystals and cooling is used to form a composite material. The mass ratio of polyamide sheet crystals to PBAT is 1:20-10,000.

Benefits of technology

While maintaining degradability, the mechanical strength of the composite material is significantly improved, solving the problem of low mechanical strength of PBAT, with the strength enhanced by about 30%, Young's modulus increased by about 80%, and the elastic modulus is 3.3 times that of the raw material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613928A_ABST
    Figure CN119613928A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to the technical field of composite materials, and particularly discloses a composite material based on degradable plastic PBAT and a preparation method thereof, the composite material comprises the following raw materials: polyamide lamellar crystal and PBAT; wherein the polyamide lamellar crystal is prepared by taking polyamide, a poor solvent and an additive as raw materials. According to the embodiment of the invention, effective combination of polyamide lamellar crystals and PBAT is realized through process design, so that the comprehensive performance of the composite material is improved while the degradability is maintained, and the problem of low mechanical strength of PBAT in application in the prior art is solved. Moreover, the preparation method provided by the embodiment of the invention is simple and has a wide market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and specifically relates to a composite material based on biodegradable plastic PBAT and a preparation method thereof. Background Art

[0002] With the increasing awareness of green development around the world, the environmental pollution caused by the difficult-to-degrade characteristics of traditional plastics has become increasingly prominent, and the research and development and application of degradable plastics have gradually become a hot spot in scientific research and industrial production. PBAT is a petroleum-based flexible thermoplastic biodegradable plastic. It is a copolymer of butylene adipate and butylene terephthalate. It has good ductility and elongation at break, as well as good heat resistance and impact resistance. It also has excellent biodegradability and is one of the most popular and best degradable materials in the research of biodegradable plastics. The final degradation products of PBAT are non-toxic carbon dioxide and water, which are harmless to the environment. It can be widely used in packaging materials, agricultural films, sanitary products and food packaging. It is an important substitute for traditional polyolefin plastics and has a very broad application prospect.

[0003] However, PBAT also has defects such as poor strength, low modulus, poor heat resistance, and slow crystallization rate, which seriously limit its promotion and application. In order to overcome the above defects, the use of additive blending is the most economical and effective method without affecting the degradation performance. By changing the material ratio, composite materials with different physical properties can be prepared to meet higher application requirements. At present, the research on PBAT modification is constantly advancing, such as improving its mechanical properties by adding cellulose nanocrystals, thermoplastic starch, etc., and improving its crystallization properties by blending with PPC. Selecting suitable materials for blending to prepare composite materials will effectively improve the various properties of PBAT and further promote the development of PBAT. Summary of the invention

[0004] The purpose of the embodiments of the present invention is to provide a solution to the problem of low mechanical strength of biodegradable plastic PBAT during application.

[0005] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions:

[0006] A composite material based on biodegradable plastic PBAT, that is, a composite material of polyamide flakes and PBAT; wherein the polyamide flakes are made from polyamide, additives and poor solvents as main raw materials.

[0007] The additive is an alkaline solution or a reducing agent solution, wherein the alkaline aqueous solution is an aqueous solution of one or more of ammonia, sodium hydroxide, potassium hydroxide, and calcium hydroxide, with a mass concentration of 0.1-10%. The reducing agent aqueous solution is an aqueous solution of one or more of vitamin C, citric acid, sodium citrate, glucose, and formaldehyde. Preferably, the aqueous solution is a sodium hydroxide solution.

[0008] Preferably, in the polyamide platelets and the poor solvent, 0.05-3 wt % of polyamide 66 is contained in every 100 ml of the poor solvent.

[0009] The poor solvent is any one or more of ethylene glycol, glycerol, butanediol, etc. The preferred poor solvent is ethylene glycol.

[0010] Another object of the embodiment of the present invention is to provide a method for preparing a composite material based on a degradable plastic PBAT, wherein the method for preparing a composite material based on a degradable plastic PBAT specifically comprises the following steps:

[0011] The polyamide flakes are mixed with a solution or melt of PBAT, cooled, and finally a polyamide flake / PBAT composite material is formed; wherein the mass ratio of the polyamide flakes to the PBAT is 1:20-10000.

[0012] Compared with the prior art, the embodiments of the present invention have the following beneficial effects:

[0013] The composite material based on the degradable plastic PBAT provided in the embodiment of the present invention uses polyamide flakes and PBAT rationally, uses PBAT solution or melt to mix with polyamide flakes and prepares the composite material of PBAT and polyamide, realizes the effective combination of polyamide flakes and PBAT, thereby improving the mechanical strength of the composite material while maintaining the degradability, and solves the problem of low mechanical strength of PBAT in the application of the prior art. Moreover, the preparation method of the composite material based on the degradable plastic PBAT provided in the embodiment of the present invention is simple and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention.

[0015] Figure 1 A stress-strain curve diagram of a biodegradable plastic PBAT composite material provided in one embodiment of the present invention.

[0016] Figure 2A stress-strain curve diagram of a biodegradable plastic PBAT composite material provided in another embodiment of the present invention.

[0017] Figure 3 A stress-strain curve diagram of a biodegradable plastic PBAT composite material provided in another embodiment of the present invention. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the following embodiments will help those skilled in the art to further understand the embodiments of the present invention, but do not limit the embodiments of the present invention in any form. It should be pointed out that for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the embodiments of the present invention. These all belong to the protection scope of the embodiments of the present invention.

[0019] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0020] First of all, it should be noted that the biodegradable plastic PBAT products currently on the market are sensitive to temperature changes due to their low glass transition temperature, resulting in a significant decrease in strength under high temperature conditions. At the same time, such materials are usually brittle and have low strength, which limits their promotion and application. In order to further improve its performance and meet the needs of more application scenarios, although composite materials can be prepared by adding materials to PBAT to enhance its mechanical strength, there is often a problem that the mechanical strength of the material cannot be improved while maintaining its degradability due to the addition of materials. Therefore, designing a composite material based on PBAT that improves the strength of the material while maintaining its degradability has become an urgent problem to be solved.

[0021] In summary, in order to solve the problem of low mechanical strength of PBAT in the prior art, an embodiment of the present invention provides a polyamide platelet / PBAT composite material, which includes the following raw materials:

[0022] Polyamide flakes and PBAT;

[0023] Wherein, the polyamide platelet is made of polyamide (PA), additives, and poor solvents as raw materials. The additive is an alkaline solution or a reducing agent, and the alkaline aqueous solution is an aqueous solution of one or more of ammonia, sodium hydroxide, potassium hydroxide or calcium hydroxide, with a mass concentration of 0.1-10%. The reducing agent aqueous solution is an aqueous solution of one or more of vitamin C, citric acid, sodium citrate, glucose or formaldehyde, with a mass concentration of 0.1-10%. A further preferred solution is to add a sodium hydroxide (NaOH) aqueous solution to the raw materials. The polyamide platelet is preferably polyamide 66.

[0024] In the embodiment of the present invention, the composite material based on the biodegradable plastic PBAT is prepared by a specific synthesis and compounding process, using polyamide flakes and PBAT as raw materials to prepare the composite material based on PBAT. By effectively regulating the ratio, the effective combination of polyamide flakes and PBAT is achieved, thereby improving the comprehensive performance of the material and solving the problem of low mechanical strength of PBAT in the prior art during application.

[0025] As another preferred embodiment of the present invention, in the polyamide, every 100 ml of the poor solvent contains 0.01-3 wt % of polyamide.

[0026] As another preferred embodiment of the present invention, in the polyamide, every 100 ml of the poor solvent contains 0.05-2 wt % of polyamide.

[0027] As another preferred embodiment of the present invention, the poor solvent is any one or more of ethylene glycol, glycerol, butanediol, etc.

[0028] Specifically, the polyamide is prepared by adding 0.05-2wt% of polyamide to 100 ml of a poor solvent (one or more of ethylene glycol, glycerol, butanediol, etc.), heating the mixture in an oil bath to 170-197° C. for 5-120 minutes to completely dissolve the mixture.

[0029] Preferably, the preparation method of the polyamide lamellae is as follows: add 0.05-2wt% of polyamide to 100 ml of a poor solvent (one or more of ethylene glycol, glycerol, butanediol, etc.), heat in an oil bath to 170-197°C and maintain for 5-120 min to completely dissolve it, then cool to 160-140°C, add 5mL-40ml of a NaOH aqueous solution (mass concentration of 0.1-10%) and continue to cool to 150-120°C and incubate at a constant temperature for 5min-12h, then cool to room temperature, filter, wash and dry to obtain polyamide lamellae.

[0030] The embodiment of the present invention provides a method for preparing a composite material based on a degradable plastic PBAT, which specifically comprises the following steps:

[0031] The polyamide flakes are mixed with a PBAT solution or a melt of a degradable plastic, and cooled to finally form a polyamide flake / PBAT composite material, that is, the PBAT-based composite material is obtained; wherein the mass ratio of the polyamide flakes to the PBAT is 1:10-10000.

[0032] In actual preparation, after the polyamide flakes are mixed with the PBAT solution, they are sprayed or coated to dry, and then cooled to form a polyamide flake / PBAT composite material. After the polyamide flakes are mixed with the PBAT melt, they are cooled to form a polyamide flake / PBAT composite material.

[0033] It should be noted that, due to its low glass transition temperature, PBAT in the prior art has the problem of low mechanical strength in application. Therefore, plasticization and toughening modification are usually required before practical application. Although composite materials can be prepared by adding materials to PBAT to enhance its mechanical strength, there is often a problem that the mechanical strength of the material cannot be improved while maintaining its degradability due to the addition of materials. Polyamide polymer materials play an irreplaceable role in many fields such as aerospace, rail transportation, electrical and microelectronics due to their wide application and excellent comprehensive performance. The embodiment of the present invention synthesizes polyamide flakes and compounds them with degradable plastics to improve the strength and toughness of the material while maintaining its degradability, thereby effectively broadening its scope of application and solving the problems of low strength, high brittleness, and high temperature sensitivity of existing degradable plastics.

[0034] Preferably, the method for preparing the composite material based on the degradable plastic PBAT comprises the following steps:

[0035] 1) Synthesis of polyamide 66 flakes: Add 0.05-2wt% of polyamide to 100 ml of poor solvent ethylene glycol, heat in an oil bath to 170-197°C and keep for 5-120 min to completely dissolve it, then cool to 160-140°C, add 0mL-40ml of NaOH aqueous solution (mass concentration is 1-50%), continue to cool to 150-120°C and incubate at a constant temperature for 5min-12h, then cool to room temperature, filter, wash and dry to obtain polyamide flakes.

[0036] 2) Mix polyamide 66 flakes with a solution or melt of PBAT. The solution is formed by dissolving PBAT in a good solvent, and the concentration can be arbitrary. The melt is formed by melting PBAT at the melting point. After the polyamide flakes are mixed with the PBAT solution, they are sprayed or coated and dried. After the polyamide flakes are mixed with the PBAT melt, they are cooled. The mass ratio of polyamide flakes to PBAT is 1:10-10000, and finally a polyamide flake / PBAT composite material is formed, that is, a composite material based on PBAT is obtained.

[0037] The embodiment of the present invention also provides an application of the above-mentioned composite material based on degradable plastic PBAT in the preparation of composite materials, which is particularly suitable for the preparation of polymer-based composite materials and can improve the mechanical strength of the composite materials.

[0038] The technical effects of the composite material based on the biodegradable plastic PBAT according to the embodiment of the present invention are further illustrated by listing specific embodiments below.

[0039] Example 1

[0040] A composite material based on degradable plastic PBAT, the preparation method of which specifically comprises the following steps:

[0041] 1) Synthesis of polyamide 66 lamellae: Add 0.2 wt% polyamide 66 to 100 ml ethylene glycol, heat to 190°C in an oil bath for 40 min to completely dissolve it, then cool to 150°C and add 20 ml of NaOH aqueous solution (mass concentration is 0.5%), continue to cool to 140°C and incubate at a constant temperature for 3 h, then cool to room temperature, filter, wash and dry to obtain polyamide lamellae.

[0042] 2) After mixing the polyamide 66 flakes with a PBAT solution (mass ratio concentration of 20%), the coating was dried, and the mass ratio of the polyamide 66 flakes to the PBAT was 1:1000, forming a polyamide 66 flake / PBAT composite material, which is the PBAT-based composite material, marked as PBAT-0.1%PA.

[0043] In order to verify the performance of the material, the PBAT-0.1%PA sample prepared in this example was subjected to performance testing. The specific test results are shown in Figure 1 As shown, Figure 1 From its stress-strain curve, it can be seen that compared with pure PBAT material, the elongation at break of PBAT-0.1%PA is only reduced by 10.3%; the strength is increased by 34%, the Young's modulus is increased by 84.5%, and the elastic modulus is 3.3 times that of the raw material.

[0044] Example 2

[0045] A composite material based on degradable plastic, the preparation method of which specifically comprises the following steps:

[0046] 1) Synthesis of polyamide 66 lamellae: Add 0.5wt% polyamide 66 to 100ml ethylene glycol, heat to 190℃ in an oil bath for 50min to completely dissolve it, then cool to 150℃ and add 0ml NaOH aqueous solution, continue to cool to 130℃ and incubate at a constant temperature for 3h, then cool to room temperature, filter, wash and dry to obtain polyamide lamellae.

[0047] 2) After mixing the polyamide 66 flakes with a PBAT solution (mass ratio concentration of 20%), the coating is dried, and the mass ratio of the polyamide 66 flakes to the PBAT is 1:800, forming a polyamide 66 flake / PBAT composite material, which is the composite material based on the degradable plastic.

[0048] Compared with pure PBAT material, the elongation at break of the sample obtained in this embodiment is reduced by 10.5%; the strength and Young's modulus are increased by 10.8% and 32.6% respectively, and the elastic modulus is 2.1 times that of the raw material.

[0049] Example 3

[0050] Compared with Example 1, except that the addition amount of polyamide 66 is 0.01wt%, the other parts are the same as Example 1, and the material is marked as PBAT-0.01%PA.

[0051] The PBAT-0.01%PA sample prepared in this embodiment was subjected to performance testing and its mechanical properties data were obtained by analysis. Compared with the pure PBAT material, the elongation at break was reduced by about 5%; the strength and Young's modulus were increased by 5% and more than 10%, respectively, and the elastic modulus was about 1.2 times that of the raw material.

[0052] Example 4

[0053] Compared with Example 1, except that the addition amount of polyamide 66 is 0.05wt%, the other aspects are the same as Example 1, and the material is marked as PBAT-0.05%PA. In order to verify the performance of the material, the PBAT-0.05%PA sample prepared in this example was tested for performance. The specific test results are shown in Figure 2 As shown, Figure 2 From its stress-strain curve, it can be seen that compared with pure PBAT material, the elongation at break of PBAT-0.05%PA is increased by 5%, the strength is increased by 7.87%, and the elastic modulus is 1.6 times that of the raw material.

[0054] Example 5

[0055] Compared with Example 1, except that the addition amount of polyamide 66 is 1 wt %, the other parts are the same as Example 1, and the material is marked as PBAT-1%PA.

[0056] In order to verify the performance of the material, the PBAT-1%PA sample prepared in this example was subjected to performance testing. The specific test results are shown in Figure 3 As shown, Figure 3 From its stress-strain curve, it can be seen that compared with pure PBAT material, the elongation at break of PBAT-1%PA is reduced by 11.26%; the strength is increased by 9.62%, and the elastic modulus is 2.5 times that of the raw material.

[0057] Example 6

[0058] Compared with Example 1, except that the addition amount of polyamide 66 is 3wt%, the other is the same as Example 1, and the material is marked as PBAT-3%PA. In order to verify the performance of the material, the PBAT-3%PA sample prepared in this example was tested for performance. The analysis results show that compared with the pure PBAT material, the elongation at break of PBAT-3%PA is reduced by about 20%; the strength is increased by more than 10%, and the elastic modulus is about 1.3 times that of the raw material.

[0059] Example 7

[0060] Compared with Example 1, except that the mass ratio of polyamide 66 flakes to PBAT is 1:10, the other aspects are the same as Example 1.

[0061] Example 8

[0062] Compared with Example 1, except that the mass ratio of polyamide 66 flakes to PBAT is 1:20, the others are the same as Example 1.

[0063] Example 9

[0064] Compared with Example 1, except that the mass ratio of polyamide 66 flakes to PBAT is 1:10000, the others are the same as Example 1.

[0065] According to the above results, it can be seen that the embodiment of the present invention significantly improves the strength and toughness of the material by compounding polyamide flakes with PBAT, while maintaining the degradability of the material. Compared with pure PBAT, the strength is increased by about 30%, the Young's modulus is increased by about 80%, and the elastic modulus is 3.3 times that of the raw material, which solves the problem of low mechanical strength of PBAT in the prior art and broadens its application range. Moreover, the preparation method provided by the embodiment of the present invention is simple, effectively broadens the composite material preparation technology, and has broad market prospects.

[0066] Finally, it should be noted that the PBAT, polyamide 66, etc. in the embodiments of the present invention are all products of existing manufacturers. For example, in this embodiment, polyamide 66 can specifically adopt a polyamide 66 product of model PA66 produced by Asahi Chemical Corporation of Japan. The above are all conventional production raw materials, which can be selected according to specific needs, and will not be described here.

[0067] The above is a detailed description of the preferred embodiments of the present invention, describing the basic principles, main features and advantages of the present invention. However, those skilled in the art should understand that the embodiments of the present invention are not limited to the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Various changes can be made within the knowledge of ordinary technicians in this field without departing from the purpose of the embodiments of the present invention. It is not necessary and impossible to list all the embodiments here. The obvious changes or modifications derived from this are still within the scope of protection of the embodiments of the present invention.

Claims

1. A composite material based on biodegradable plastic PBAT, characterized in that: The composite material includes the following raw materials: polyamide flakes and PBAT; wherein the polyamide flakes are prepared from polyamide, additives, and poor solvents, and the additives are alkaline solutions or reducing agent solutions.

2. The composite material based on degradable plastic PBAT according to claim 1, characterized in that: The alkaline aqueous solution is one or more aqueous solutions of ammonia, sodium hydroxide, potassium hydroxide, and calcium hydroxide; the reducing agent aqueous solution is one or more aqueous solutions of vitamin C, citric acid, sodium citrate, glucose, and formaldehyde.

3. The composite material based on the degradable plastic PBAT according to claim 2, characterized in that: The mass concentration of the alkaline solution or the reducing agent solution is 0.1-10%.

4. The composite material of degradable plastic PBAT according to claim 3, characterized in that: In the polyamide and the poor solvent, every 100 ml of the poor solvent contains 0.01-3 wt % of the polyamide.

5. The composite material based on the degradable plastic PBAT according to claim 4, characterized in that: The poor solvent is any one or more of ethylene glycol, glycerol and butanediol.

6. The composite material based on the degradable plastic PBAT according to claim 5, characterized in that: The polyamide is selected from any one of polyamide 56, polyamide 66, polyamide 6 and polyamide 46.

7. A method for preparing a composite material based on degradable plastic PBAT according to any one of claims 1 to 6, characterized in that: The following steps are involved: The polyamide flakes are mixed with a solution or melt of PBAT, and cooled to obtain the PBAT-based composite material; wherein the mass ratio of the polyamide flakes to the PBAT is 1:20-10000.

8. The method for preparing a composite material based on degradable plastic PBAT according to claim 7, characterized in that: In the method for preparing the composite material based on the degradable plastic PBAT, the mass ratio of polyamide flakes to PBAT is 1:10-10000.

9. The method for preparing a composite material based on degradable plastic PBAT according to claim 8, characterized in that: In the method for preparing the composite material based on degradable plastic, the mass ratio of polyamide flakes to PBAT is 1:1000.

Citation Information

Patent Citations

  • Industrial production method of spherical polyamide powder

    CN104119546A

  • Composite thin film and method for preparing same

    CN107618245A

  • Dispersive micron-sized strip-shaped polyamide material as well as preparation method and application thereof

    CN119613953A

Cited By

  • Dispersive micron-sized strip-shaped polyamide material as well as preparation method and application thereof

    CN119613953A